Burnout Belajar selama masa Pandemi Covid 19 pada Siswa Kelas X di SMA Negeri 6 Kota Kupang - Pawe, Maria Florida; Upa, M. D. Pua; Geradus, Uda; Masi, Lolang M. (Prodi Bimbingan Konseling FKIP UNDANA, 2023)
Burnout is one of the symptoms of saturation that occurs in a person caused by there internal and external influences are influences that originated from and within his own self, while external influences are influences caused by other people and the surrounding environment. Internal factors also occur in class X high school students in Negeri 6 City The purpose of this study was to determine the shape of the aspects of learning burnout during the covid 19 pandemic for class X students at SMA Negeri 6 Kota Kupang. This study uses a quantitative approach with descriptive research methods. The population in this study were the students of class X in SMA Negeri 6 Kupang and a sample of 42 students was taken from the sampling technique. The data collection method used is the burnout questionnaire instrument which consisted of 58 items. The validity of the learning burnout scale during the pandemic covid 19 is declared valid by reliability (931). The data analysis technique used is Product Momen Correlation Analysis by using the SPSS Version 16.0 program. For data analysis, used the percentage descriptive analysis technique.